Global trends of laser bone ablation: bibliometric analysis of publications from 1979 to 2023 - Zhang, Kai-Jun; Liu, Qi; Zhang, Teng; Shen, Anjie; Han, Wei; Li, Jinqi; Zhao, Bin; Wang, Junqiang (Frontiers in Surgery, 2025)
ObjectivesThe objective of the bibliometric analysis was to quantify and identify the current status and trends of laser bone ablation research from 1979 to 2023.Materials and methodsThe Web of Science (WOS) core collection database was used to search for articles on laser bone ablation published from 1979 to 2023. The collected data were then imported into Microsoft Excel, VOSviewer, and CiteSpace for detailed analysis and visualization.ResultsA total of 383 articles were included for analysis. The United States made the most significant contributions to the field in terms of both quantity and quality. Moreover, Cattin, Philippe C emerged as the author with the highest number of publications, while the University of Basel stood out as the institution with the greatest publication output. Lasers in Surgery and Medicine emerged as not only the journal with the most publications but also held considerable influence within its domain. Prominent keywords that surfaced frequently included “ablation,” “er:yag laser,” and “bone.”ConclusionThe annual number of publications in the field of laser bone ablation is showing an overall upward trend. Research on laser bone ablation primarily focuses on investigating the parameters of this technique, as well as its application in treating bone tumors, performing laser stapes surgery, and various applications of laser bone ablation. The laser osteotomy, laser ablation of bone tumors, animal experiments, and the interaction with biological tissues during laser bone ablation are expected to be the focal areas and future directions in this field.